2010
DOI: 10.1007/s12020-010-9363-z
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor 30 in tumor development

Abstract: Estrogen plays several important physiological and pathological functions in not only reproductive system but many other systems as well. Its transcriptional activation has been traditionally described as being mediated by classic nuclear estrogen receptors (ERs). It is however established recently that a novel functional estrogen transmembrane receptor, G protein-coupled receptor 30 (GPR30), modulates both rapid non-genomic events and genomic transcriptional events of estrogen. It has been demonstrated that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 80 publications
1
50
0
4
Order By: Relevance
“…GPR30 signaling contributes to tumor growth and resistance to antiestrogen in breast cancers (51). Furthermore, GPR30 cooperates with EGFR/HER2, a gene known to be overexpressed in endocrine-resistant breast cancer, to mediate signaling pathway activation and cell proliferation (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…GPR30 signaling contributes to tumor growth and resistance to antiestrogen in breast cancers (51). Furthermore, GPR30 cooperates with EGFR/HER2, a gene known to be overexpressed in endocrine-resistant breast cancer, to mediate signaling pathway activation and cell proliferation (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPR30 is involved in drug resistance, which is often occurring during cancer treatment. Hence, simultaneous blocking both GPR30 and classic ERs may be a better strategy for the treatment of schistosomiasis-related cancer and infertility [46].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…GPR30 is independent of ERα status in breast cancer cells and tissue samples, and its action differs from the classical nuclear ERs, ERα and ERβ (32). Upregulation and activation of GPR30 promotes the progression of breast cancer, and GPR30 is considered a biological target for innovative therapeutic strategies (33). Research has demonstrated that overexpression of GPR30 in primary tumors is positively correlated with the metastatic phenotype of breast cancer (6,7), and GPR30 knockout MMTV-PyMT mice possess less aggressive tumors and fewer metastases (8).…”
Section: Discussionmentioning
confidence: 99%